Symbolic university life: discourse, dynamics and interactions at a distance in an educational organization in pandemic - Mandujano Contreras, Susana; Sandoval Núñez, Lucia (Emerging Trends in Education, 2022)
Educational organizations in the last two years have been affected by the social phenomenon that spread throughout the world by the virus called SARS-CoV-2, highlighting that, although in all organizations in our country actions prevailed under an emerging situation of suspension of face-to-face classes at all levels, little is known about the actions taken to maintain their stability and to be able to face a number of problems to to subsist in the face of the great health problems and economic deprivation that arose as a result; each organization in particular, had a different way of excelling. This work was carried out under a qualitative approach of a descriptive type through the narrative, analysis of the discourse and the symbolic life of the actors of this organization we will be able to understand the solutions applied to face the challenges before an emerging change to solve the conflicts of the reorganization of their university life. Such. is the case of this technological institution that under the gaze of organizational studies we will observe how it applied the adaptability of its symbolic life from the traditional to the technological, all from the perspective and approach of the actors called: institution, teachers and students. Keywords Symbolic life; interaction; institutional identity; Pandemic; educational institution